Benign breast diseases: experience at a teaching hospital in rural India - G., Abhijit M.; D, Anantharaman; Bhoopal, Sumanth; Ramanujam, Ranjani (International Journal of Research in Medical Sciences, 2017)
Background: Though benign breast diseases are very common with nearly 1/3 of women suffering some time during their life time, not many studies have focused on this entity, especially in rural areas. Our teaching hospital situated amongst the villages in rural part of India provided the right background for the study. Objective: To determine the frequency of benign breast diseases in a teaching hospital situated in the rural setting and to analyze the role of triple assessment in assessing benign breast diseases. Study design: Prospective, descriptive study. Setting: MVJ Medical College and Research Hospital, Hoskote, Bangalore Rural district, Karnataka, India. Method of study: Data including age, complaints, clinical examination, radiological investigations and histopathological diagnosis was collected from patients presenting to the department of surgery with breast complaints. Patients with carcinoma of the breast were excluded from the study. Results: A total of 110 patients were studied between November 2009 to March 2011. Mean age of patients was 28.6 years. Fibroadenoma was the most common diagnosis in 56.4% followed by fibroadenosis in 20.9%. There was one case each of lipoma, tuberculosis and duct ectasia and two cases of atypical ductal hyperplasia. The sensitivity of clinical diagnosis in our study was 91.1% and FNAC was 100% accurate in all patients with fibroadenoma but had a sensitivity of only 78% in the diagnosis of fibroadenosis. Only 3.3% of cases of fibroadenoma were treated conservatively.